Research Hotspots in Mitochondria-Related Studies for AKI Treatment: A Bibliometric Study - Yang M; Huang Y; Tang A; Zhang Y; Liu Y; Fan Z; Li M (Dove Medical Press, 2024)
Mengfan Yang,1,* Youqun Huang,1,* Anqi Tang,1 Yu Zhang,2 Yu Liu,3 Zhenliang Fan,4 Mingquan Li1 1Department of Nephrology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, People's Republic of China; 2Department of Nephrology, Shaanxi Provincial Hospital of Traditional Chinese Medicine, Xi'an, Shaanxi Provincial, People's Republic of China; 3Department of Nephrology, South China Hospital, Health Science Center, Shenzhen University, Shenzhen, People's Republic of China; 4Department of Nephrology, The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Mingquan Li, Department of Nephrology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan Province, People's Republic of China, Email limingquan@cdutcm.edu.cnPurpose: Acute kidney injury (AKI) is a common clinical critical condition that has become a significant healthcare burden. In recent years, the relationship between AKI and mitochondria has attracted increasing attention. Protecting mitochondria or restoring their function has emerged as a novel therapeutic strategy for alleviating AKI. This study aims to analyze and summarize the current status, research trends, and hotspots in this field, providing references and directions for future research.Methods: AKI and mitochondria-related literature from the Web of Science core collection were retrieved and collected. Bibliometric and visualization analyses were conducted using Microsoft Excel 2021, bibliometric tools (VosViewer, Citespace 6.3.R1, and the bibliometrix R package), R 4.3.2, and SCImagoGraphica software.Results: A total of 2433 publications were included in this study. The number of annual publications in this field has increased year by year. China and the United States are the two most productive countries. Central South University is the most influential research institution in terms of research output, and Parikh SM, Schnellmann RG, and Dong Z are the most influential authors in this field. KIDNEY INTERNATIONAL, JOURNAL OF THE AMERICAN SOCIETY OF NEPHROLOGY, and AMERICAN JOURNAL OF PHYSIOLOGY-RENAL PHYSIOLOGY are the most influential journals. Initially, the research focused on keywords such as oxidative stress, ischemia-reperfusion injury, apoptosis, inflammation, and autophagy. In recent years, new research hotspots have emerged, including ferroptosis, aging, mitochondrial quality control, messenger RNA, mitochondrial-targeted antioxidants, extracellular vesicles, and nanodrug delivery.Conclusion: Research on the relationship between mitochondria and AKI has broad developing prospects, and targeting mitochondrial regulation will become a focus of future AKI prevention and treatment research.Keywords: acute kidney injury, mitochondria, bibliometric analysis, visualization, VOSviewer, citespace